2022
DOI: 10.30802/aalas-jaalas-21-000081
|View full text |Cite
|
Sign up to set email alerts
|

Extended-release Buprenorphine, an FDAindexed Analgesic, Attenuates Mechanical Hypersensitivity in Rats (Rattus norvegicus)

Abstract: A new extended-release buprenorphine (XR), an FDA-indexed analgesic, has recently become available to the laboratoryanimal community. However, the effectiveness and dosing of XR has not been extensively evaluated for rats. We investigatedXR’s effectiveness in attenuating postoperative hypersensitivity in a rat incisional pain model. We hypothesized that highdose of XR would attenuate mechanical and thermal hypersensitivity more effectively than the low dose of XR in this model. We performed 2 experiments. In e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
1
10
1
Order By: Relevance
“…In this current study, differences in thermal hypersensitivity testing on the contralateral thigh found in the Bup-SR, XR-Lo, and XR-Hi groups as compared to Saline group, at 1, 4, 8, and 24 h are likely due to sedation from the treatment drugs. Although sedation was not clinically evident in this study, it has been previously noted in the literature when administering Bup-SR or XR-Hi to rats [ 28 , 29 , 34 ].…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…In this current study, differences in thermal hypersensitivity testing on the contralateral thigh found in the Bup-SR, XR-Lo, and XR-Hi groups as compared to Saline group, at 1, 4, 8, and 24 h are likely due to sedation from the treatment drugs. Although sedation was not clinically evident in this study, it has been previously noted in the literature when administering Bup-SR or XR-Hi to rats [ 28 , 29 , 34 ].…”
Section: Discussionmentioning
confidence: 47%
“…Therefore, we decided to evaluate XR-Hi as compared to Bup-SR in neonatal rodents. Our group has found that XR-Hi effectively attenuates post-operative pain for 48 h in adult mice [ 25 ] and adult rats [ 28 ] using the plantar incisional model. Such a difference between Bup-SR and XR-Hi in the duration of attenuating pain may be attributed to the technological differences between the two drugs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations